Collaborative governance in stunting interventions at the local level - Anna Khuzaimah; Ulfa Kurniati; Muhammad Zhohirul Haq; Yunita (Department of Government Science, 2024)
This study aims to determine and evaluate Collaborative Governance implemented by the government, private sector and the community in handling stunting in Enrekang Regency. The research method used is a descriptive qualitative approach to describe and analyze data obtained through interviews, observations, documentation and literature studies with a purposive sampling method related to the implementation of Collaborative Governance of the Enrekang Regency Government. The data analysis technique used is qualitative analysis through data reduction, data presentation and data verification. The results showed that based on Collaborative Governance by Emerson, it is known that the stakeholders involved have implemented the Dynamics, Actions and Impact and Adaptation of Collaboration well. However, some of the components in it still need to be evaluated and maximized. Among them are the Collaboration Dynamics which still have obstacles in the form of deliberations that have not run optimally and parties who do not know about existing procedures and collective agreements. This certainly affects the Collaborative Action which makes low involvement from several other actors and ultimately also has an impact on the lack of maximum stunting reduction. This study promotes equitable collaboration among all stakeholders to enhance the success of stunting prevention programs and foster active participation from all involved parties.